Insights into the Lunar Imbrium Basin Mare Units by Characterizing Their Regolith Property, Chronology, and Composition - Shuangshuang Wu; Jianping Chen; Feng Zhang; Cheng Zhang; Xiaojian Xu (The Planetary Science Journal)
Mare basalts are volcanic products that filled the large topographic depressions on the Moon. Investigating volcanic activity aids in deeply understanding the lunar endogenic geological processes and thermal evolution over time. Previous studies on lunar volcanism mainly focused on using optical, spectral, and topographical data, which are good at analyzing lunar surface morphology and composition, but detection of its subsurface regolith property has been greatly restricted. Chang′E-2 microwave radiometer data can reveal the thermal and dielectric properties of mare deposits to variable depths and identify potential lava flows, providing a new perspective for delineating volcanic units. This work presents a comprehensive analysis of the regolith properties, chronology, and composition of mare basalts in the Imbrium basin, aiming to reveal the details of the basin’s volcanic history and thermal evolution. Trend surface analysis was applied to remove latitude effects, generating detrended brightness temperature difference (dTB) maps that distinctly highlight major mare deposits. We identified Imbrium mare units using detrended dTB maps, which effectively capture the diurnal temperature variations. Results show at least three major episodes of lava filling events in the basin, approximately occurring at 3.51 Ga, 3.26 Ga, and 2.76 Ga, respectively. Although the range of compositions varied in each eruption, the general trend suggests an increasingly highly evolved composition for the mare deposits emplaced in the Imbrium basin over time. The updated geological map provides detailed regional background information for understanding the evolution of the Imbrium basin.